2018
DOI: 10.1016/j.techfore.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Technology and value network evolution in telehealth

Abstract: Vesselkov, Hämmäinen, and Töyli formed the idea, constructed models and scenarios. Vesselkov conducted the interviews and wrote the paper. Hämmäinen and Töyli edited the text.Publication IV: "Design and governance of mHealth data sharing" Vesselkov formed the idea, collected the data, conducted interviews and wrote the paper. Hämmäinen and Töyli provided comments on the analysis and edited the text.Publication V: "Internet of things (IoT) platform competition: consumer switching versus provider multihoming" Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 124 publications
0
14
0
Order By: Relevance
“…There was no mechanism for physicians or hospitals to constantly evaluate patients' health and make appropriate suggestions. Remote diagnostics and monitoring in healthcare are now possible due to the increasing prevalence of IoT-connected medical devices and other related technology such as machine learning, artificial intelligence (AI), cloud computing and blockchain, which serve to keep patients safe and healthy while enabling medical professionals to provide better care (Biswas et al, 2020;Khalemsky and Schwartz, 2017;Vesselkov et al, 2018). As interactions with physicians have grown simpler and more efficient, telehealth through IoT has also improved patient involvement and satisfaction (Khodadad-Saryazdi, 2021).…”
Section: Science Mappingmentioning
confidence: 99%
See 2 more Smart Citations
“…There was no mechanism for physicians or hospitals to constantly evaluate patients' health and make appropriate suggestions. Remote diagnostics and monitoring in healthcare are now possible due to the increasing prevalence of IoT-connected medical devices and other related technology such as machine learning, artificial intelligence (AI), cloud computing and blockchain, which serve to keep patients safe and healthy while enabling medical professionals to provide better care (Biswas et al, 2020;Khalemsky and Schwartz, 2017;Vesselkov et al, 2018). As interactions with physicians have grown simpler and more efficient, telehealth through IoT has also improved patient involvement and satisfaction (Khodadad-Saryazdi, 2021).…”
Section: Science Mappingmentioning
confidence: 99%
“…Prior research has shown that IoT has application areas that benefit patients, communities, physicians, healthcare facilities and insurance providers (Hsiao et al, 2019;Khalemsky and Schwartz, 2017;Pan et al, 2019;Schwartz et al, 2017;Sneha and Varshney, 2009). Wearable technologies such as fitness trackers and other wirelessly linked devices such as cardiovascular monitoring devices and glucometers enable patients to get customized treatment (Aboelmaged et al, 2021;Vesselkov et al, 2018). These gadgets can be programed to remind users of calorie counts, activity checks, medical appointments and blood pressure changes, among others (Ben Arfi et al, 2021;Pan et al, 2019).…”
Section: Science Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital health services do improve the efficiency of the entire healthcare system with enhanced service quality, decreased response time, and an improvised post discharge schedule, resulting in the satisfaction of patients, clinicians, and hospitals ( Laurenza et al., 2018 ; Liu et al., 2018 ; Lu et al., 2021 ; Miao et al., 2017 ; Senot et al., 2016 ). A few other studies discussed the importance of healthcare information technologies in the collection, safety, privacy, and analysis of the huge healthcare data generated in discharging e-health and telemedicine services ( Vesselkov et al., 2018 ; Villalba-Mora. et al., 2015 ; Wang et al., 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The term "mHealth" first appeared in 2003 and describes the "medical and public health practice supported by mobile devices"(Kay et al 2011). The concept comprises a broad range of technologies, including wireless, mobile, wearable and healthcare apps(Vesselkov et al 2018). In recent years a large number of mHealth apps have been developed and widely used, making mobile technologies emerge as a powerful tool in the health care industryZakhem et al 2018) and there is a rising demand for mobile apps with AI services(Ji Wang et al 2018).Artificial intelligence systems simulate the human mind by learning, reasoning and performing self-correction, and these systems can even be more accurate than physicians in diagnosis in specialties such as surgery, radiology, dermatology and intensive care(Goldhahn & Spinas, 2018).…”
mentioning
confidence: 99%